The Impacts of Cardiac Rehabilitation Exercise Therapy in Patients Following Percutaneous Coronary Intervention: Systematic Review - Amanda, Rana Zhafira; Adwiarto, Sarah Khairunnisa; Purwowiyoto, Sidhi Laksono (Annals of Clinical Cardiology, 2024)
Abstract Background: Cardiac rehabilitation (CR) is a vital evidence-based intervention for improving quality of life and reducing adverse outcomes in patients with coronary artery disease (CAD) post-percutaneous coronary intervention (PCI), addressing persistent risks such as high mortality and recurrent angina despite advancements in PCI. Objective: This study focused on establishing the impact of cardiac rehabilitation (CR) exercise therapy following percutaneous coronary intervention (PCI) with multiple vital outcomes. Methods: A comprehensive search was performed across databases, including ScienceDirect, PubMed, PMC, and Cochrane, with a restriction to the English-language articles. The focus was on randomized controlled trials (RCTs) that evaluated the effects of CR exercise therapy in patients who underwent PCI - comparing the group that participated in CR exercise therapy with those that received routine care. Key outcomes evaluated included laboratory values, left ventricular ejection fraction, 6-min walk test, quality of life (QoL), cardiopulmonary function, exercise capacity, and cardiovascular events. The Cochrane RoB 2 was utilized to evaluate the quality of the study. Outcomes were synthesized qualitatively to summarize the effects of CR on the estimated parameters. Results: This review included 12 RCTs from several countries involving 1215 patients - 605 in control groups and 610 in intervention groups. Nine studies categorized some concerns in the overall assessment, and three RCTs were classified as low risk of bias. Results showed that patients with CR intervention effectively experience positive impacts across all key outcomes. Conclusion: CR benefits coronary artery disease patients post-PCI by managing cardiovascular risk factors, improving heart function, reducing cardiovascular events, and enhancing QoL.